Ketamine and neuroticism: a double-hit hypothesis of internalizing disorders - N. McNaughton; P. Glue (Personality Neuroscience, 2020)
Psychiatric disorders can often be viewed as extremes of personality traits. The primary action of drugs that ameliorate these disorders may, thus, be to alter the patient’s position on a relevant trait dimension. Here, we suggest that interactions between such trait dimensions may also be important for disorder. Internalizing disorders show important differences in terms of range of activity and speed of response of medications. Established antidepressant and anxiolytic medications are slow in onset and have differing effects across different internalizing disorders. In contrast, low-dose ketamine is rapidly effective and improves symptom ratings in all internalizing disorders. To account for this, we propose a “double hit” model for internalizing disorders: generation (and maintenance) require two distinct forms of neural dysfunction to coincide. One hit, sensitive to ketamine, is disorder-general: dysfunction of a neural system linked to high levels of the personality trait of neuroticism. The other hit is disorder-specific: dysfunction of one of a set of disorder-specific neural modules, each with its own particular pattern of sensitivity to conventional drugs. Our hypothesis applies only to internalizing disorders. So, we predict that ketamine will be effective in simple phobia and (perhaps partially) in anorexia nervosa, but would make no such prediction about other disorders where neuroticism might also be important secondarily (e.g. attention deficit hyperactivity disorder and schizophrenia).